Mode preference hypothesis in the context of mixed-mode survey design - Rybak, Adam (Methodological critique in the practice of knowledge creation, 2019)
The aim of this chapter is to show the state of knowledge in the field of mixed-mode survey design methodology, the known theoretical and practical issues in its use, and to highlight knowledge gaps on this subject. Inclusion of survey mode preference hypothesis in this context is particularly interesting because of possible positive effects of its proper implementation on increasing response rates and measurement quality and lowering survey costs. However, this phenomenon is still not deeply understood and lacks a well-developed theoretical context. This chapter connects it with a wider range of theories of survey participation and gathers the elements of possible future theory. In conclusion, it presents a possible strategy for the utilization of knowledge about participants’ preferences concerning a mode in survey research.